Implementation of The Teams Games Tournament (TGT) Type Cooperative Learning Model to Improve Learning Outcomes - Dewi, Imega Syahlita; Lestari, Adhelia (Science Education and Application Journal, 2024)
Implementation of the Teams Games Tournament (Tgt) Type Cooperative Learning Model to Improve Learning Outcomes . This research aims to find out whether the Teams Games Tournament (TGT) learning model can improve student learning outcomes. The research design used was a classroom action research (PTK) design. The research carried out was Class Action Research (PTK). The population of this study included all students of class X TITL 1 SMKN 1 Nganjuk with a total of 3 6 students , carried out in 2 cycles. The data analysis techniques used are quantitative and qualitative analysis. The results of data analysis show that there has been an increase in the average score of the student learning outcomes test from 77.7 to 79.9 and classical completeness from 69% with the incomplete category to 92% classical completeness. Thus, the researcher did not take any more action in cycle III